Assessment of high-resolution regional ocean reanalysis K-ORA22 for the Northwest Pacific - Inseong Chang; Young Ho Kim; Young-Gyu Park; Hyunkeun Jin; Gyundo Pak; Jae-Il Kwon; You-Soon Chang (Progress in Oceanography, 2024)

Simulation Characteristics of Ocean Predictability Experiment for Marine environment (OPEM): A Western North Pacific Regional Ocean Prediction System - Hyunkeun Jin; Young Ho Kim; Young-Gyu Park; Inseong Chang; You-Soon Chang; Hyukmin Park; Gyundo Pak (Ocean Science Journal, 2024)

Comparison of Summer Coastal Currents off the East Coast of Korea in 2021 and 2022 - Seung-Woo Lee; Gyundo Pak; Jae-Hyoung Park; Su-Chan Lee; Jin-Yong Jeong; Suyun Noh (Journal of Marine Science and Engineering, 2024)
This study investigates the variability of coastal currents off the east coast of Korea, specifically in the Wangdolcho area of the East/Japan Sea, from June 2021 to October 2022. The observations revealed significant fluctuations in depth-averaged current velocity, with a peak of 0.81 m/s in August 2021 and a minimum of −0.05 m/s in August 2022. These year-to-year variations highlight the complex dynamics of coastal currents influenced by regional wind patterns and mesoscale eddies. In the summer of 2021, the development of offshore eddies, coupled with variable alongshore wind stress, led to increased current velocities and alternating upwelling and downwelling conditions, resulting in abrupt changes in current intensity. Conversely, in the summer of 2022, the negative vorticity in the Korea Strait and negative wind stress curl along the coast likely caused the East Korean Warm Current to shift further offshore, resulting in a weakened southward flow along the coast. This study emphasizes the need for long-term monitoring to better understand the coastal current dynamics and their environmental impacts. The anticipated completion of the Wangdolcho Ocean Research Station is expected to greatly improve monitoring capabilities, providing continuous and comprehensive data that will enhance our understanding of coastal currents and their broader impacts on the marine environment.

Optimal Proxy Indices for Annual Marine Heatwave Characteristics Using Monthly Sea Surface Temperature - Gyundo Pak (Ocean Science Journal, 2024)

Quantification of the extremely intensified East Korea Warm Current in the summer of 2021: offshore and coastal variabilities - Gyundo Pak; Kyung-Jae Lee; Seung-Woo Lee; Hyunkeun Jin; Jae-Hyoung Park (Frontiers in Marine Science, 2023)
In this study, we investigate the record-breaking intensification and abrupt weakening of the East Korea Warm Current (EKWC) in the summer of 2021. We analyzed the ocean data assimilation products resolving this event to examine the association between the abrupt changes in the EKWC and various oceanic/atmospheric factors. The results indicate that during the summer of 2021, the EKWC extended northward beyond its climatology, reaching up to 40°N with the maximum speed of 1.16 m s -1 on August 1. In mid-August, the EKWC underwent a rapid weakening, returning to its climatological level. We could attribute the temporal variability in the anomalous EKWC in 2021 to the distinct temporal variability in the dynamic height anomalies between coastal and offshore regions. The offshore variability in the dynamic height anomaly, which is related to warm eddy variability, led to an anomalously increased EKWC velocity (up to 0.59 m s -1 ) during the EKWC peak velocity period in 2021. However, anomalous coastal downwelling induced by a weak northerly wind anomaly decelerated the EKWC by -0.06 m s -1 in the same period. In mid-August, a typhoon-related northerly wind induced a sudden rise in the coastal dynamic height anomaly, resulting in a rapid weakening of the EKWC. Our findings suggest that changes in geostrophic current related to warm eddies and typhoons have substantially contributed to the temporal variability in the EKWC, improving our understanding of the temporal variability in the western boundary currents.

Impact of satellite and regional in-situ profile data assimilation on a high-resolution ocean prediction system in the Northwest Pacific - Inseong Chang; Young Ho Kim; Hyunkeun Jin; Young-Gyu Park; Gyundo Pak; You-Soon Chang (Frontiers in Marine Science, 2023)
The impacts of observation data sets on the high-resolution (1/24°) Northwest Pacific prediction system were investigated with the model sensitivity tests. We compared the model experiments assimilating the different combinations of the observation data sets, such as the sea surface height derived from satellite altimetry, sea surface temperature, and in-situ profiles, based on the Ensemble Optimal Interpolation. Pseudo-profiles constructed by the method of Cooper and Haines (1996, CH96) were assimilated into the model to assimilate sea surface height data. CH96 applied a conservation principle to derive pseudo-profiles by rearranging preexisting profiles. The comparison of the model experiments suggests that each observation data set enhances the model performance. Especially, the assimilation of the sea surface height reduces the model error by more than 9.81% and 6.44%, respectively, in terms of the root-mean-square error of the ocean temperature and salinity in the subsurface layer. It is interesting that the assimilation of the in-situ temperature profiles in the Korean marginal seas contributes to improving the reproducibility of the subsurface temperature and salinity in the East/Japan Sea (EJS) as well as Kuroshio-Kuroshio Extension (K-KE) regions. The improvement in the K-KE region seems to be related to the reproducibility of the Kuroshio axis. As the water mass in the EJS flows into the Pacific Ocean through the Tsugaru Strait, it affects the front of the Sanriku confluence, and it seems to eventually control the Oyashio Current and Kuroshio axis. In conclusion, this study evaluated the contribution of each observation component to ocean analysis in the KOOS-OPEM and confirmed the role of the existing observation networks. This study also suggests that greater attention should be paid to the role of regional ocean observation networks to improve the forecast skill of the ocean prediction system not only in the region but also in the open ocean, such as the Pacific Ocean.

Governing factors of the record-breaking marine heatwave over the mid-latitude western North Pacific in the summer of 2021 - Gyundo Pak; Joocheul Noh; Young-Gyu Park; Hyunkeun Jin; Jae-Hyoung Park (Frontiers in Marine Science, 2022)
During July of 2021, the sea surface temperature of the mid-latitude western North Pacific had increased by five degrees over 10 days. This high temperature was maintained for approximately a month before it disappeared rapidly in approximately five days. The underlying mechanisms of this unprecedented marine heatwave event have not yet been researched through a quantitative approach. The development and decay processes of the marine heatwave event were investigated using heat budget analysis and one-dimensional modeling. In mid-July, an anomalous high-pressure atmospheric circulation, affecting to the reduced cloud coverage and increased solar radiation, anchored where the marine heatwave occurred. The increased solar radiation accompanied by the weakened wind reduced the vertical mixing and resulted in a thinner mixed-layer, which accelerated the sea surface warming. The impact of reduced mixing is as important as the increase in solar radiation. In mid-August, typhoon-induced entrainment mainly caused sea surface cooling. The wind-driven mechanical mixing between warm surface water and cooler subsurface water lowered the SST. Additionally, evaporative cooling by strong winds, which drives buoyancy-driven vertical mixing, contributed to the decay of the MHW. The effect of mechanical mixing on cooling is comparable to that of buoyancy-driven mixing.

Korea Institute of Ocean Science and Technology Earth System Model and Its Simulation Characteristics - Gyundo Pak; Yign Noh; Myong-In Lee; Sang-Wook Yeh; Daehyun Kim; Sang-Yeob Kim; Joon-Lee Lee; Ho Jin Lee; Seung-Hwon Hyun; Kwang-Yeon Lee; Jae-Hak Lee; Young-Gyu Park; et al. (Ocean Science Journal, 2021)

Comparisons of Net Heat Flux Data Sets Over the Western North Pacific - Gyundo Pak; Jae-Hyoung Park; Seok-Joon Lee; Young-Gyu Park; You-Soon Chang (Ocean Science Journal, 2020)

Lagrangian Approach for a New Separation Index of the East Korea Warm Current - Gyundo Pak; Young Ho Kim; Young-Gyu Park (Ocean Science Journal, 2019)